ISLAM AND RELIGIOUS MODERATION: THE ROLE OF SCHOOL LABORATORY IN NEGOTIATING RELIGIOUS MODERATION WITHIN THEOLOGICAL PLURALITY - Mohammad Rindu Fajar Islamy (UIN Raden Mas Said Surakarta, 2021)
This study aims to explore the implementation process of religious moderation carried out by the High School Laboratory of the Universitas Pendidikan Indonesia through its learning process. As an open educational institution, this school accepts students from various backgrounds, including the term of their religion. Encountering various ideologies in one learning platform is predicted to trigger tensions between religious adherents. But in fact, this school laboratory can minimize those potential tensions through various approaches. Based on an ethnographic approach, wherein the data gathered through intensive observation and in-depth interviews with several key informants, the results of this study reveal that the efforts made by school principals and teachers through strengthening the understanding of religious moderation concept, which is implemented into learning curricula and teaching models inside and outside of the school classroom, it turns out to be able to make students moderate and tolerant.